The Energy Covenant: Energy Dominance and the Rhetoric of the Aggrieved - Schneider, Jen; Peeples, Jennifer (Frontiers in Communication, 2018)
The Trump Administration has adopted “energy dominance” as its guiding ideology for energy policy, marking a notable shift from decades of “energy security” rhetoric. This paper analyzes how Secretary of Interior Ryan Zinke, one of the administration’s key spokespeople for energy dominance, uses “energy covenant renewal” to frame the importance of energy dominance for the conservative base. Covenant renewal is a modified form of the jeremiad; Zinke uses it to unite conservative identities around energy politics and policies. Energy dominance thus invites those who feel aggrieved under Obama administration regulatory policy and the multicultural identity politics of the left to renew their commitment to fossil fuels, American exceptionalism, and a restored social order and privilege.